Effective Treatment of a Malignant Breast Phyllodes Tumor with Doxorubicin-Ifosfamide Therapy - Shinya Yamamoto; Shigeru Yamagishi; Toshiro Kohno; Ryosuke Tajiri; Toshikazu Gondo; Noboru Yoshimoto; Nobuko Kusano (Case Reports in Oncological Medicine)
Malignant phyllodes tumors of the breast occur infrequently and are difficult to treat with chemotherapy. Here, we present an effective chemotherapy strategy for recurrent malignant breast phyllodes tumors. A 48-year-old woman was diagnosed with a malignant phyllodes tumor in her right breast and underwent total right mastectomy. One year later, the tumor recurred in the right (a 2.2 cm mass) and left (a 10 cm mass) lungs; pleural effusion was also observed in the left lung. Eight courses of doxorubicin-ifosfamide (AI) therapy were administered. After treatment, the right lung mass and pleural effusion regressed completely and the left lung mass regressed to 2 cm. In conclusion, AI therapy is useful for treating recurrent malignant breast phyllodes tumors.